Social capital in context of cooperation - Starosta, Paweł (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
The aim of the article is to present the basic concepts of social capital in mutual cooperation context. The analytically distinguished main components of this concept are presented; social networks, trust and norms. Further in the text, attention is focused on discussing two types of functions that social capital performs; generative and associative functions. The conclusion presents the main controversies related to various concepts of social capital as well as the application of this concept in the practice of empirical research. We are mainly concerned with dilemmas related to the processes of social alienation, controversies around investment and consumption awareness, the issue of normative neutrality and the role of social capital in development processes as well. The basic source for the presented text is the literature included in articles and books on social capital.